2013
DOI: 10.4304/tpls.3.12.2315-2321
|View full text |Cite
|
Sign up to set email alerts
|

English Language Proficiency as a Predictor of Academic Achievement among Medical Students in Iran

Abstract: In Iran, many changes have been made in English language teaching. In academic grounds it is important to know the correlation between the expertise of students in English and their scores in different scientific subjects, before applying any further curriculum reform. The present study was designed to determine the correlation between English language proficiency and the achievement of medical students in their national comprehensive basic science exam (NCBSE). One hundred and fifty six students admitted in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 25 publications
(18 reference statements)
5
14
0
Order By: Relevance
“…This finding illustrates that there is a direct relationship between these two variables and that English proficiency is a determinant of academic success for students at the BUE. This finding is in accordance with other research findings (Maleki & Zangani, 2007;Sivaraman et al, 2014;Sadeghi et al, 2013;Roche & Harrington, 2013) amongst others. Since English is the medium of instruction at the BUE, for students to be able to engage effectively in their academic studies and perform well, they must be able to read, write, listen and speak at a level appropriate to their studies on entry to the university.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…This finding illustrates that there is a direct relationship between these two variables and that English proficiency is a determinant of academic success for students at the BUE. This finding is in accordance with other research findings (Maleki & Zangani, 2007;Sivaraman et al, 2014;Sadeghi et al, 2013;Roche & Harrington, 2013) amongst others. Since English is the medium of instruction at the BUE, for students to be able to engage effectively in their academic studies and perform well, they must be able to read, write, listen and speak at a level appropriate to their studies on entry to the university.…”
Section: Discussionsupporting
confidence: 94%
“…), this study presented evidence to show that as the student's English language proficiency increases so does their academic success. This finding is in accordance with the results of other studies (Sahragard et al, 2011;Maleki & Zangani (2007); Sadeghi et al, 2013). As shown in Table 4, comparing the four English levels (Pre-Intermediate, Intermediate, Upper Intermediate and Advanced) with grade bands (A, B, C, D & F), students entering the university at the Upper Intermediate and Advanced levels have performed better than those in the lower English levels.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Other studies from Iran have reported similar findings. For example, Maleki and Zangani (2007) found a significant connection between proficiency and grade point averages of academic achievement of students majoring in English translation while Sadeghi et al (2013) found that proficiency in English Language could significantly influence academic achievement of medical students.…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…Because of this increased international immigration, the number of non-English speaking students attending English language schools has also increased (Faltis, 2014;Kim & Helphinstine, 2017). Moreover, English language proficiency has been described as a challenge to academic achievement in countries around the world, including Australia (Watkins, Razee, & Richters, 2012), Germany (Brandenburg et al, 2016), Canada (Roessingh & Douglas, 2012), and Iran (Sadeghi, Kashanian, Maleki., & Haghdoost, 2013).…”
Section: Introductionmentioning
confidence: 99%